56. Arizona and Adjacent New Mexico - Charles A. Anderson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1968)
Arizona and western New Mexico contain 17 of the 25 leading copper mines in the United States. Production of molybdenite, lead, zinc, and by-product gold and silver is important. Precambrian ore deposits are largely limited to the Yavapai Series in central Arizona and most of the metal production has come from massive sulfide deposits, dominantly pyritic but containing different amounts of chalcopyrite, tennantite, sphalerite, and galena. Their origin has been interpreted by some geologists as hydrothermal replacement of schist, and by others as syngenetic deposits later metamorphosed. Most of the important ore deposits are of Mesozoic and early Tertiary age, dominated by the porphyry copper deposits spatially related to stocks, plugs, sills, or dikes of quartzbearing porphyritic to granular rocks. Host rocks for these deposits include the associated intrusive rocks, Precambrian schist and granitic rocks, Paleozoic limestones, Mesozoic(?) porphyritic andesite, and Mesozoic arkose and siltstone. Chalcopyrite and pyrite are the dominant hypogene sulfide minerals in the porphyry copper deposits, accompanied by minor molybdenite. The Questa deposit in New Mexico is largely molybdenite. Supergene sulfide minerals are chalcocite and minor covellite. Some ore bodies consist largely of hypogene sulfides, some are dominantly supergene sulfides, and others are mixed hypogene-supergene sulfides. Supergene oxide-copper minerals locally are important. Intense hydrothermal alteration accompanied the metallization in all of the porphyry copper deposits; five types are recognized, ( 1) propylitic, (2) argillic, (3) potassic, ( 4) quartz-sericite (without clay), and (5) lime silicate. The origin of the closely spaced fractures that contain ore minerals in intersecting veinlets is debatable; some geologists favor tectonic forces and others suggest cooling of magma or shrinkage due to alteration. Breccia pipes, veins, and limestone replacements account for some important deposits of Mesozoic and early Tertiary age, and presumably these are genetically related to the various intrusive rocks of this age. The St. Anthony deposit of Cenozoic age in southeastern Arizona is unique, consisting of a lead-zinc vein associated with later molybdenum and vanadium oxide-minerals. Cenozoic manganese deposits in western Arizona are an important resource in the Artillery Mountains, but the extent to which they may be exploited is a metallurgical and economic problem.